Rapid onset of functional tic-like behaviors among adolescent girls—Minnesota, September–November 2021 - Firestone, Melanie J.; Holzbauer, Stacy; Conelea, Christine; Danila, Richard; Smith, Kirk; Bitsko, Rebecca H.; Klammer, Susan M.; Gingerich, Stefan; Lynfield, Ruth (Frontiers in Neurology, 2023)
Background: On October 15, 2021, the Minnesota Department of Health began investigating a school cluster of students experiencing tic-like behaviors thought to be related to recent COVID-19 infection. The objective of this report is to describe the investigation, key findings, and public health recommendations. Methods: Affected students and proxies were interviewed with a standardized questionnaire including validated depression and anxiety screens. Results: Eight students had tic-like behaviors lasting >24 hours after initial report with onset during September 26–October 30, 2021. All eight students were females aged 15–17 years. All students either had a history of depression or anxiety or scored as having more than minimal anxiety or depression on validated screens. Four students previously had confirmed COVID-19: the interval between prior COVID-19 and tic symptom onset varied from more than a year prior to tic symptom onset to at the time of tic symptom onset. Conclusion: The onset of tic-like behaviors at one school in Minnesota appeared to be related more to underlying mental health conditions than recent COVID-19. These findings highlight the need to better understand functional tic-like behaviors and adolescent mental health.